Poéticas mestiças: a representação de raça e de mestiçagem em performances selecionadas de Paulo Nazareth - SIMONE BEATRIZ DE PAULA VAZES (2022)
The present work aims to analyze the performances Authentic Mixed Man (2008); Cruzeiro do Sul – acredito que seja a cor da minha pele (2010); Banana Market / Art Market (2011) e Antropologia do Negro (2014) of Paulo Nazareth that materializes the notion of race and of miscegenation and, through this investigation, the conceptual, aesthetic and discursive choices of the works, searching for possible positions, criticisms and artistic interpretations about the identity, representation and stereotypes that surround the mestizo theme mainly in the brazilian context. Considering the importance given to miscegenation as one of the central points for the formation of brazilian national identity, artistic representations, in their most diverse languages, often offered a romantic perspective on the multiracial formation of the brazilian population. The artist Paulo Nazareth (1977-) is then dedicated to investigating poetically, in his travels between geographic and symbolic territories, the associated ideas around the figure of the mestizo, racial violence, confrontation and similarity between different folks. The theoretical framework used as a support for the study expands from authors such as RoseLee Goldberg (1984; 2006; 2007), Jorge Glusberg (2013) and Renato Cohen (2002), who will serve as a focus for conducting bibliographic research on the artistic language of performance; the theoretical exploration of other fields of research. knowledge will be approached to deepen some terms related to the issue of race and miscegenation, such as whitening, identity and myth of the three races, through the studies and reflections of Lilia Schwarcz (1993; 1994; 1996; 1998; 2012a; 2012b; 2015; 2019), Kabengele Munanga (2000; 2015), Renato Ortiz (1986; 2006), in addition to other authors; who deal with racial issues and are crucial for the development of critical studies of miscegenation. Keywords: Paulo Nazareth; Race; Miscegenation; Performance; Contemporary Art.